Gene Therapy 2.0: Harnessing Cutting-Edge Technologies for Precision Medicine - Gaurav Kumar Mahto; Tanya Sharma; Shubam Singh; Kamalesh Mistry; Md. Aftab Alam; Neha Nahid (International Journal of Genetic Modifications and Recombinations, 2025)
Somatic gene therapy has become the standard form of gene therapy; this creates the Gene Therapy 2.0 era. This new and distinct time consists in the new-generation genome-editing tools and markers, more efficient systems for gene delivery, and personalized medicine approaches that raise the efficacy and safety of the treatment. Base and prime editing are two types of CRISPR-based gene editing tools have provided high precision and reduced off-target effects while editing the targeted genes. These RNA based therapeutics include mRNA therapy, antisense-oligonucleotide therapy, RNAi therapy which add more dimension to the list of treatable diseases and aliments. The advancements in growth of viral and non viral vectors like adeno-associated viruses, lentiviral vectors, lipid nanoparticles and exosome based carriers make the gene transfer more efficient and have minimum immunogenic responses. Actual use of Gene Therapy 2.0 is already seen by successful treatments for monogenic diseases like spinal muscular atrophy, hemophilia, and inherited retinal diseases. Further, new therapeutics include oncology treatments, neurodegenerative disorders and & rare genetic disorders which expand the therapeutic section. However, some resistant problems are immunological responses, toxicity of vectors, and ethical issues about germline modifications. Governments such as the USA (FDA) and Europe (EMA) have continue to modify its policies about gene based therapeutic products. Now apart from artificial intelligence, the computational modeling is being used in gene therapy to increase the efficiency and accuracy of the treatment. As progress is made, Gene Therapy 2.0 is set to revolutionise disease treatment and care with long standing, potentially disease curing approaches to a wide range of otherwise untreatable diseases.
Keywords: CRISPR; Gene therapy; Genome Editing; Personalized medicine; Precision medicine; RNA Therapeutics; Viral Vectors; artificial intelligence; clinical applications; genetic disorders